THE INTERPLAY BETWEEN PERFORMANCE BONDS AND THE PRINCIPLE OF INDEPENDENCE OF THE BANK'S COMMITMENT IN JORDAN - Emad Mohammed Al-Amaren; Che Thalbi Bt Md. Ismail; Mohd Zakhiri bin Md. Nor (Faculty of Law, Universitas Sebelas Maret, 2019)
As the wide range of international trade out-turn and diversity of the parties, causing banks have to create a new credit service, that is bank guarantees, to enhance the trust between the parties. By providing the security and ease, the beneficiary will obtain a certain amount of money from the bank and being independent from the other party. While the committed party provides insurance to the beneficiary as a guarantee for the implementation or good performance in accordance with agreed terms, in this situation, performance bonds are crucial to be considered as this tool has the principle of independence regarding the bank’s commitment, as such, could clarify one party obligation to provide money, services or goods to another party. Taking performance bonds as solution whereby accompanied the Guaranty (Al Kafala) and subordination imposed by the legal system, the lacunae of legal rules which govern performance bonds has created difficulties and may lead Judges to create the new relevant law. This article is aimed at studying how the Jordanian Judiciary deals with performance bonds, since there is no previous legal rules governing such bank contract.